CfT-1, An LTR-Retrotransposon in Cladosporium fulvum, a fungal pathogen of tomato - McHale, M.; Roberts, I.; Noble, S.; Beaumont, C.; Whitehead, M.; Seth, D.; Oliver, Richard (1992)
A retrotransposon from the fungal tomato pathogen Cladosporium fulvum (syn. Fulvia fulva) has been isolated and characterised. It is 6968 by in length and bounded by identical long terminal repeats of 427 bp; 5 by target-site duplications were found. Putative first- and second-strand primer binding sites were identified. Three long open reading frames (ORFs) are predicted from the sequence. The first has homology to retroviral gag genes. The second includes sequences homologous to protease, reverse transcriptase, RNAse H and integrase, in that order. Sequence comparisons of the predicted ORFs indicate that this element is closely related to the gypsy class of LTR retrotransposons. Races of the pathogen exhibit polymorphisms in their complement of at least 25 copies of the sequence. Virus-like particles which co-sediment with reverse transcriptase activity were observed in homogenates of the fungus. This is the first report of an LTR retrotransposon in a filamentous fungus.